2020
DOI: 10.1161/hypertensionaha.119.13929
|View full text |Cite
|
Sign up to set email alerts
|

L-(+)-Ergothioneine Significantly Improves the Clinical Characteristics of Preeclampsia in the Reduced Uterine Perfusion Pressure Rat Model

Abstract: Preeclampsia is a multifactorial hypertensive disorder of pregnancy founded on abnormal placentation, and the resultant placental ischemic microenvironment is thought to play a crucial role in its pathophysiology. Placental ischemia because of fluctuations in the delivery of oxygen results in oxidative stress, and recent evidence suggests that mitochondrial dysfunction may be a prime mediator. However, large clinical trials of therapeutic antioxidants such as vitamins C and E for the treatment of preeclampsia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 47 publications
1
40
0
1
Order By: Relevance
“…A recent paper indicates that ERG relieves the effects seen in a rat model of the pregnancy disorder pre-eclampsia (597) . D. B. K. decided to bring together the multifaceted contributions of the various authors listed.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…A recent paper indicates that ERG relieves the effects seen in a rat model of the pregnancy disorder pre-eclampsia (597) . D. B. K. decided to bring together the multifaceted contributions of the various authors listed.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…Studies have also suggested that ET is protective in preeclampsia, a hypertensive disorder during pregnancy that results in placental ischemia, by protecting against reperfusion-induced oxidative stress and inflammation, preserving mitochondrial function, and reducing hypertension in a reduced uterine perfusion pressure rat model of preeclampsia [ 65 , 66 , 154 ]. Conversely, mice deficient in OCTN1 (whose tissues are completely devoid of ET) are more susceptible to intestinal ischemia and reperfusion injury, with higher inflammatory markers and mortality compared with wild-type animals [ 101 ].…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%
“…Ergothioneine reduces the risk of PE [ 161 ], primarily by mitigating iron-induced oxidative stress. In a rat model of PE, ergothioneine ameliorated hypertension, reduced mitochondrial-specific H 2 O 2 in the kidneys, and increased the fetal weight [ 162 ].…”
Section: Antioxidant Therapies In Pementioning
confidence: 99%